Gender Disparities in ICT Beliefs and Usage Among Learners in Basic Public Schools in Urban Slums in Ghana - Baako, Issah; Osei, Eric Opoku; Abroampa, Winston Kwame (INSTED: Interdisciplinary Studies in Education & Society, 2025)
This study examines gender disparities in beliefs about and the usage of Information and Communications Technology (ICT) among students in basic public schools in urban slums in Ghana. A mixed-methods approach with a concurrent research design was employed, collecting data from 379 junior high school (JHS) students across 20 schools in 11 urban slums within two cities. Data collection tools included a self-administered structured questionnaire that utilized a five-point Likert-type scale and a lesson observation schedule. The data was analyzed using t-tests of independent samples and Pearson correlation in IBM SPSS version 26. The findings indicate that students have very high beliefs in ICT, evidenced by a mean score of 4.41, demonstrating their strong conviction in technology’s potential to enhance education. However, disparities in ICT usage were apparent, with a mean score of 3.18 and a standard deviation of 1.33. The Pearson correlation analysis revealed a very weak but statistically significant positive relationship between students’ beliefs in ICT and their ICT usage (r = 0.127, p = 0.014), suggesting that stronger beliefs in the educational value of technology may modestly increase usage frequency. Gender comparisons showed no significant differences in ICT beliefs between male (M = 30.87, SD = 3.59) and female learners (M = 30.78, SD = 3.88), t(370) = 0.20, p = 0.84. Similarly, no significant differences were found in ICT usage between males (M = 26.15, SD = 6.58) and females (M = 24.83, SD = 6.87), t(368) = 1.88, p = 0.06, although males reported slightly higher usage levels. This study underscores the potential of ICT to transform education in resource-constrained environments while highlighting the limited impact of gender on ICT beliefs and usage. The findings suggest that addressing barriers to ICT access and usage, rather than focusing solely on gender, may be crucial for achieving equitable technology integration in education.